A novel method for simulating dynamic facades to analysing, and optimizing daylight and visual comfort in office buildings - Mehran Shahmoradi; Mansour Yeganeh (Results in Engineering)
Visual comfort analysis for a dynamic facade is complicated and requires more time and resources to find the shading device's optimum position for every hour of the year. This paper intends to show an optimization method to reach visual comfort for the entire year for single office rooms with a nearly fully glazed south side covered by a dynamic shading device. First, a genetic algorithm optimized 63 h of a year separately. Then, the shading device's optimum (state of a shading device that leads to gaining high indoor illumination while controlling glare level) position for all sample hours was collected. Mathematica software gets these results of sample hours data as inputs and operates the data fitting process on them. Finally, it gives 12 two-variable functions (surface function) based on the sun's position parameters (x: azimuth, y: altitude) to shading device indices; then, these can predict the entire year's ideal position for the shading device. Formulas are based on format; to find the optimum position of louvers, we just put the sun's position parameters into functions. For example, on the 21st of June, in hours 9:00, 12:00, and 15:00 by this method, we achieved UDI respectively: 90.714 - 60.714 - 89.286 while DGP was acceptable without any need for optimization process but with the GA method after numerous simulations achieve respectively to UDI: 91.033 - 64.402 - 91.848. This method precasts the ideal value for shading device indices for 94 % of a year's hours and omits the need for a simulation or optimization process for every single hour of a year.